Consent in the endoscopy department. Issue 4 (6th February 2014) - Mohanaruban, Aruchuna; Flanders, Lucy; Dor, Riaz
Abstract : The demand for endoscopic procedures continues to increase and is likely to continue to do so for the foreseeable future. Alongside elective diagnostic procedures, the number of complex and therapeutic procedures is increasing. It is therefore vital that the consent process is comprehensive, and high standards in consenting patients are maintained. Consent is defined as a patient's agreement to treatment or an intervention proposed by a health professional. Careful patient selection is required when proposing endoscopic procedures with an appreciation of the risks and complications that are involved. This paper addresses the various components of gaining informed consent and the legal issues surrounding this process. Additionally, this article reviews legislation and focuses upon specific instances where further considerations have to be made; in a patient who lacks capacity, in children, in percutaneous endoscopic gastrostomy and in the patient who is a Jehovah's Witness.